COVID-19 pandemic in Indonesia: Situation and challenges of rehabilitation medicine in Indonesia - Boya Nugraha; Luh Karunia Wahyuni; Hening Laswati; Peni Kusumastuti; Angela BM Tulaar; Christoph Gutenbrunner (Acta Medica Indonesiana)
Abstrak